Epididymal Fat-Derived Sympathoexcitatory Signals Exacerbate Neurogenic Hypertension in Obese Male Mice Exposed to Early Life Stress. Issue 5 (November 2021) - Dalmasso, Carolina; Leachman, Jacqueline R.; Ghuneim, Sundus; Ahmed, Nermin; Schneider, Eve R.; Thibault, Olivier; Osborn, Jeffrey L.; Loria, Analia S.
Abstract : Previously, we have shown that male mice exposed to maternal separation and early weaning (MSEW)—a mouse model of early life stress—display increased mean arterial pressure compared with controls when fed a high-fat diet. As the stimulation of sensory nerves from fat has been shown to trigger the adipose afferent reflex, we tested whether MSEW male mice show obesity-associated hypertension via the hyperactivation of this sympathoexcitatory mechanism. After 16 weeks on high-fat diet, MSEW mice displayed increased blood pressure, sympathetic activation, and greater depressor response to an α-adrenergic blocker when compared with controls ( P <0.05; n=8), despite no differences in adiposity and plasma leptin. The acute infusion of capsaicin in epididymal white adipose tissue (1.5 pmol/μL of capsaicin, 8 μL/per site, 4 sites, bilaterally) increased the total pressor response in MSEW mice compared with controls (110±19 versus 284±33 mm Hg×30 minutes; P <0.05; n=8). This response was associated with neuronal activation in OVLT, posterior paraventricular nucleus of the hypothalamus, and RVLM ( P <0.05 versus control; n=6–7). Renal denervation abolished both the acute and chronic elevated mean arterial pressure in obese MSEW mice. Moreover, selective sensory denervation of epididymal white adipose tissue using resiniferatoxin (10 pmol/µL solution; n=6) decreased mean arterial pressure in obese MSEW mice only ( P <0.05 versus control). Obese MSEW mice displayed increased epididymal white adipose tissue levels of both tryptophan hydroxylase (Tph1) mRNA expression and its synthesis product serotonin (8.3±1.9 versus 16.6±1.7 ug/mg tissue; P <0.05 versus control). Thus, afferent sensory signals from epididymal white adipose tissue may contribute to the exacerbated fat–brain–blood pressure axis displayed by obese male mice exposed to early life stress. Abstract : Supplemental Digital Content is available in the text.